Charting an integrated course to enhance Indonesian seafarers' quality and well-being by optimizing safety culture, legal protection, training, and working conditions - Sudewo, Gatot Cahyo; Jinca, Muhammad Yamin; Sukardiman, Tjuk; Octora, Theresya Yoanyta (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
A comprehensive solution through an integrated strategic management approach, focusing on these four elements can be optimized simultaneously. Legal protection, training, and improving working conditions and safety culture will create a safer and more productive environment, realizing optimal mental health performance and seafarer quality. Quantitative approach through Structural Equation Modelling (SEM) with the help of AMOS software. Data were obtained from a survey involving 280 seafarers, shipping company managers, and industry regulators. The AMOS SEM analysis technique evaluated the direct and indirect relationships between the variables. Legal protection, training, working conditions, and safety culture have a significant influence on the mental health and quality of Indonesian seafarers. Structural model analysis showed a good fit to the data and interactions between variables. The findings support implementing integrated management strategies to improve seafarers' well-being and performance in the shipping industry.